FLUCTUATING ASYMMETRY REFLECT THE GROWTH OF HYBRID GROUPER Epinephelus fuscoguttatus AND Epinephelus polyphekadion - Ketut Sugama; Ahmad Muzaki; I Gusti Ngurah Permana; Haryanti Haryanti (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Fluctuating asymmetry has been widely used as a measure of developmental stability and as an indicator of individual fish growth. The present study compared fluctuating asymmetry in three bilateral meristic traits of F-1 hybrid between female Epinephelus fuscoguttatus and male Epinephelus polyphekadion and two F-1 pure parental progenies. The fishes were reared by communal and separate tank systems. Hybrids were confirmed by allozymes electrophoresis. After three months of rearing, the F-1 hybrids fish grew faster 45.9% and 66.6% compare to the F-1 pure parental progenies of E. fuscoguttatus and E. polyphekadion (P<005) respectively. Development stability as measured by fluctuating asymmetry was lower in hybrid (20%-40%) than in the pure parental progenies (53%-80%). Among four enzyme loci examined, only Pgm locus showed variants and at that locus all hybrids fish were heterozygous. Heterozygous hybrids showed lower fluctuating asymmetry and related to higher developmental stability. The higher developmental stability positively reflected a faster growth rate. Thus this finding can be used to explain the reason that why hybrids groupers appeared grew faster than parental species.